The legend of Korra. Book one : Air / [videorecording (DVD)]. - Faustino, David, 1974-; Simmons, J. K.; Blum, Steve, 1965-; Varney, Janet, 1976-; Baker, Dee Bradley; Byrne, P. J., 1974- (Paramount Pictures, 2013)
When Avatar Aang passes, he is reincarnated as a girl named Korra, from the Southern Water Tribe. Korra leaves the safety of her home to travel to Republic City. Before long, Korra's Avatar skills are put to the test when she encounters a group of Chi-blockers led by a masked man named Amon. With his Equalists followers, Amon plots to gain control over Republic City and ultimately rid the world of the 'impurity' of bending. Korra and her friends will stop at nothing to capture him.